PENGARUH PENGHINDARAN PAJAK TERHADAP NILAI PERUSAHAAN YANG DIMODERASI OLEH CORPORATE GOVERNANCE DAN KEPEMILIKAN MAYORITAS - Tiara Ulfa Inanda; Eddy Suranta; Pratana Puspa Midiastuty (Jurnal Akuntansi, 2018)
This study aims to provide empirical evidence about the effect of tax avoidance on firm value is moderated by corporate governance and majority shareholder. This study using a sample of 13 non-financial companies that listed on Corporate Governance Perception Index (CGPI) ranking list. This research uses 3 hypotheses. data were analyzed using multiple linear regression using SPSS 22.0 program. The results showed that tax avoidance has no significant effect on firm value, corporate governance that moderates tax avoidance affects the firm's value and the majority shareholder that moderates tax avoidance does not affect the firm's value.